(untitled) (World Bulletin of Social Sciences, 2025)
This study explores the emergence and formation of the comedy genre in Eastern literature. Particular attention is given to the importance of traditional folk performances such as puppetry, clowning, and satirical shows, which served as the foundation for the development of comedic elements. Although classical Uzbek literature did not have a clearly defined comedy genre, it included satirical works that resemble comedy. The research examines the opinions of medieval scholars on this genre and emphasizes the significant role played by the Jadid movement in creating the earliest examples of comedic plays in Uzbek literature.